LCA Foods 2022. 113th lnternational Conference on Life Cycle Assessment of Food - Vazquez Rowe, lan (2022)
The 13th International Conference on LCA of Food, which was held on October 11-14 2022, took place for the first time in the Latin America-Caribbean region, in Lima, Peru. The theme of the conference were the topics aligned to: The Role of Emerging Economies in Global Food Security. LCA Food 2022 venue's welcomed more than 250 participants through a hybrid modality, presenting 6 outstanding keynote speakers, and accepting peer-reviewed submissions in both oral and poster modality as part of 28 parallel sessions. The organizing committee was led by the research group PELCAN (Peruvian LCA and Industrial Ecology Network), part of the Department of Engineering at Pontificia Universidad Católica del Perú and assisted by the INTE - PUCP. In the following link, you can find a revisit of the conference experience on our PELCAN's youtube channel.